Distinguishing Models of Professional Development: The Case of an Adaptive Model's Impact on Teachers' Knowledge, Instruction, and Student Achievement. (January 2015) - Koellner, Karen; Jacobs, Jennifer
We posit that professional development (PD) models fall on a continuum from highly adaptive to highly specified, and that these constructs provide a productive way to characterize and distinguish among models. The study reported here examines the impact of an adaptive mathematics PD model on teachers' knowledge and instructional practices as well as on students' achievement over time. Results indicate at least modest impacts in each of these areas. Our findings demonstrate that adaptive models of PD can be subjected to investigations of impact based on quantitative research methodologies; moreover, we argue that utilizing a wider variety of methodologies to study adaptive models is increasingly needed as these models gain in popularity and usage.